2009
DOI: 10.1007/s10615-009-0239-8
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Peer Attachment in Minority Males at High Risk for Delinquency

Abstract: Juvenile delinquency and high risk behaviors have been linked to disturbances in attachment. The present study examined parent and peer attachment in 67 African American males and 97 Latinos (ages 12-17, M = 14.7 ± 1.3) attending an alternative school. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…Juvenile delinquency remains a serious problem in today's society (Hoeve et al 2011; Van der Laan et al 2010;Wampler and Downs 2010). Adolescent boys with a minority background account for a large share in juvenile crime both in the United States as well as in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile delinquency remains a serious problem in today's society (Hoeve et al 2011; Van der Laan et al 2010;Wampler and Downs 2010). Adolescent boys with a minority background account for a large share in juvenile crime both in the United States as well as in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding attachment can help one understand how individuals process social interactions, (Dykas & Cassidy, 2011) such as school and according to Wampler and Downs (2010) form friendships. The different types of attachments influences these interactions and friendships as it has been found those with secure attachments can share with peers and can work through distressing events (Waters et al, 1979) and grow up to be responsible and compassionate (Orlans & Levy, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…By not needing reassurance from others, they avoidant individuals can be seen as hostile due to their lack of reliance on others and no desire for assistance. The feelings and behaviors described above stem back to the tenets of attachment style where it has been found that affected by attachment style are formations of friendship, romantic love and future parenting styles (Wampler & Downs, 2010).…”
Section: Effects Of Attachment On Peer Relationships and Psychologicamentioning
confidence: 99%
See 2 more Smart Citations